A Comparative Study to Assess the Effectiveness of oil Massage versus Pelvic Floor Exercise versus Jacobson’s Relaxation Technique on Dysmenorrhea and Perceived Stress among Adolescent Girls Studying at Selected Colleges of Bengaluru, Karnataka - Veena, M. (International Journal of Nursing Research, 2023)
Background of the Study: Adolescence is the time between the commencement of puberty and the start of adulthood. Menarche is a significant occurrence in the lives of adolescent females because it is one of the signals that puberty has begun. Puberty is marked by a series of physical and mental changes. Toward the end of adolescence, menstrual abnormalities are a regular occurrence. About 75% of females have some form of monthly problem, such as painful, irregular, delayed, or heavy menstrual bleeding. Materials and Methods: Quantitative research approach was used in the study, 300 adolescent girls having problem of dysmenorrhea was selected as a samples. Quasi-experimental (comparative study) research design with three groups pre-test and post-test design approach was used as a research design. In this study probability, purposive sampling technique was utilized. Results: The study results in pre-test mean 26.79 and SD5.55, post-test mean 12.1 and SD 5.99 for oil massage on dysmenorrhea level, pre-test mean 21.17 and SD 6.91, post-test 14.75 and SD 6. Oil massage on perceived stress. The results show significant Effectiveness (P < 0.05). Pelvic floor exercise on dysmenorrhea pre-test shows mean 25.63 and SD 5.95, while post-test shows mean 7.74 and SD 6.45. The pre-test showed mean 21.96 and SD 6.43, while the post-test showed mean 13.12 and SD 6.49. Pelvic floor exercise on level of perceived stress, the resultsshow significant effectiveness (P < 0.05). For Jacobson’s relaxation technique Pre-test showed mean 26.63 and SD 5.59, whereas post-test showed mean 8.65 and SD 6.90. Level of perceived stress, with pre-test mean 22.67 and SD 6.32 and post-test mean 11.86 and SD 6.66 results show significant Effectiveness (P < 0.05). Conclusion: This means that oil massage therapy, pelvic floor exercises, and Jacobson’s relaxation techniques are effective ways to reduce Dysmenorrhea and Perceived Stress, even pelvic floor exercises are better than oil massage therapy and Jacobson’s relaxation technique for reducing dysmenorrhea, oil massage therapy and Jacobson’s relaxation technique are better for reducing stress in teenage girls than pelvic floor exercises and oil massage therapy